Effects of aging processes at the surface of the superconductor β − FeSe - Lanoël, L. (2022)
This work reports a complete analysis of surface degradation in β-FeSe single crystals; which includes the dependence on aging and temperature of Raman spectra, electrical transport resistivity, and XPS depth profiling characterization. All measurements are consistent with the emergence of clusters of Se and the presence of FeOx in the surface of the crystals. The vibrational modes of the Se clusters are coupled to the β-FeSe ones as seen in the structural transition. Moreover, this degraded surface can behave like a quasi-two-dimensional layer, as supported by a theoretical model and also consistent with Raman spectra. While the degradation of thin films of β-FeSe in air is widely known, with a corresponding loss of the superconducting properties, in single crystals with aged surfaces we observe an enhancement of the superconducting properties.